The 2D Android Game ‘Bung Tomo Adventure’ uses the Finite State Machine Method - Doan Oggie Adriansz; Agung Panji Sasmito; Deddy Rudhistiar (Journal of Enhanced Studies in Informatics and Computer Applications, 2026)
Educational games are an effective media to improve the youth’s understanding on national history, especially when the game is presented in an interactive and engaging manner. The adoption of Finite State Machines (FSM) in 2D games makes the game to be more realistic and more dynamic. This research aims to develop an Android-based ‘Bung Tomo Adventure’ game by adopting the FSM method to control character’s behavior and to enhance the user's playing experience. The research methodologies include literature review, system’s design, coding using Godot Engine, Black Box Testing, device testing, and user evaluation. Besides that, the Black Box testing outcome shows that the game features work as expected. The user experience testing shows that 87% respondents gave positive response (categories Good and Average), which means this game is quite well received especially in terms of storyline and ease of play, although some aspects such as visual appearance and game distribution need more improvement.